2020
DOI: 10.1111/jph.12906
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Neopestalotiopsis fungi associated with a novel leaf fall disease of rubber trees (Hevea brasiliensis) in Thailand

Abstract: A novel leaf fall disease of rubber trees (Hevea brasiliensis) has been recently noted in Thailand. The fungal pathogens of this disease were identified based on both morphological and molecular characteristics as Neopestalotiopsis cubana and N. formicarum. Portions of internal transcribed spacer (ITS) region and the large subunit (LSU), translation elongation factor 1‐α (TEF1‐α) and β‐tubulin (TUB) genes were PCR amplified with the primer pairs ITS1/ITS4, LR0R/LR5, EF1‐728F/EF2 and T1/Bt2b, respectively. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…There were three groups that commonly be studied as Pestalotiopsis, Pseudopestalotiopsis, and Neopestalotiopsis. Neopestalotiopsis can be differed from Pestalotiopsis and Pseudopestalotiopsis from the versicolourous character of media cells [18]. To ensure the species of isolate X1 needed advanced analyses using molecular study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were three groups that commonly be studied as Pestalotiopsis, Pseudopestalotiopsis, and Neopestalotiopsis. Neopestalotiopsis can be differed from Pestalotiopsis and Pseudopestalotiopsis from the versicolourous character of media cells [18]. To ensure the species of isolate X1 needed advanced analyses using molecular study.…”
Section: Resultsmentioning
confidence: 99%
“…Neopestalotiopsis species were known as endophytic, parasitic, and saprobic fungi [2,10]. Currently, some of them were most as parasitic [22,9,18]. As an endophytic and parasitic fungus, Neopestalotiopsis had been reported that the host was the plant, not yet was reported from the mushroom.…”
Section: Resultsmentioning
confidence: 99%
“…Plant pathogens recently causing emerging diseases in Thailand were obtained from Culture Collection of Pest Management, Faculty of Natural Resources, Prince of Songkla University; details are provided in Table 1 . Airborne pathogens were cultured on PDA for three days before being subjected to bioassay: Corynespora cassiicola , causing leaf spots on lettuce [ 25 ]; Neopestalotiopsis clavispora , causing flower blight on anthurium [ 26 ]; and Neopestalotiopsis cubana , causing leaf fall in rubber trees [ 27 ]. The soilborne pathogen was Sclerotium rolfsii , causing stem rot in Jerusalem artichoke.…”
Section: Methodsmentioning
confidence: 99%
“…A total of ten symptomatic stem canker samples of H. polyrhizus were collected from a dragon fruit plantation field in Phatthalung Province, southern Thailand (7 • 45 24.2 N, 99 • 58 47.2 E), kept in a plastic bag in an ice box and taken to a plant pathology laboratory, where isolation was subsequently conducted. The isolation of fungal pathogens was conducted by tissue transplantation according to the method of Pornsuriya et al [14]. Small pieces (2-3 mm) of infected tissue were surface disinfected with 0.5% sodium hypochlorite (NaOCl) [13], rinsed three times with sterilized distilled water (DW), air-dried, placed on water agar (WA), and incubated for 24 h at 28 ± 2 • C. Hyphal tips were cut and transferred to potato dextrose agar (PDA), incubated at ambient temperature (28 ± 2 • C) with natural light-light cycle and subsequently used for further methods.…”
Section: Sample Collection and Pathogen Isolationmentioning
confidence: 99%
“…Thailand is located in tropical and subtropical regions where the weather favors disease spread [8,9]. Several emerging diseases have been isolated and reported to cause diseases in several plant species in this area in the past 5 years [10][11][12][13][14][15][16][17]. However, the identification of fungal pathogens causing diseases on H. polyrhizus in Thailand is rarely documented.…”
Section: Introductionmentioning
confidence: 99%